Adaptive threshold harvesting and the suppression of transients. (21st April 2016) - Segura, Juan; Hilker, Frank M.; Franco, Daniel
Abstract: Fluctuations in population size are in many cases undesirable, as they can induce outbreaks and extinctions or impede the optimal management of populations. We propose the strategy of adaptive threshold harvesting (ATH) to control fluctuations in population size. In this strategy, the population is harvested whenever population size has grown beyond a certain proportion in comparison to the previous generation. Taking such population increases into account, ATH intervenes also at smaller population sizes than the strategy of threshold harvesting. Moreover, ATH is the harvesting version of adaptive limiter control (ALC) that has recently been shown to stabilize population oscillations in both experiments and theoretical studies. We find that ATH has similar stabilization properties as ALC and thus offers itself as a harvesting alternative for the control of pests, exploitation of biological resources, or when restocking interventions required from ALC are unfeasible. We present numerical simulations of ATH to illustrate its performance in the presence of noise, lattice effect, and Allee effect. In addition, we propose an adjustment to both ATH and ALC that restricts interventions when control seems unnecessary, i.e. when population size is too small or too large, respectively. This adjustment cancels prolonged transients. Abstract : Highlights: We present an adaptive harvesting strategy to reduce population fluctuations. The strategy is useful for exploited species or to prevent outbreaks. It provides an alternative to adaptive limiter control . Transient dynamics can profoundly raise the short-term yield. We propose adjusted control strategies that reduce the length of transients.